Integration of High-Throughput Imaging and Multiparametric Metabolic Profiling Reveals a Mitochondrial Mechanism of Tenofovir Toxicity. Issue 1 (24th December 2022) - Pearson, Adam; Haenni, Dominik; Bouitbir, Jamal; Hunt, Matthew; Payne, Brendan A I; Sachdeva, Ashwin; Hung, Rachel K Y; Post, Frank A; Connolly, John; Nlandu-Khodo, Stellor; Jankovic, Nevena; Bugarski, Milica; et al.
Abstract: Nephrotoxicity is a major cause of kidney disease and failure in drug development, but understanding of cellular mechanisms is limited, highlighting the need for better experimental models and methodological approaches. Most nephrotoxins damage the proximal tubule (PT), causing functional impairment of solute reabsorption and systemic metabolic complications. The antiviral drug tenofovir disoproxil fumarate (TDF) is an archetypal nephrotoxin, inducing mitochondrial abnormalities and urinary solute wasting, for reasons that were previously unclear. Here, we developed an automated, high-throughput imaging pipeline to screen the effects of TDF on solute transport and mitochondrial morphology in human-derived RPTEC/TERT1 cells, and leveraged this to generate realistic models of functional toxicity. By applying multiparametric metabolic profiling—including oxygen consumption measurements, metabolomics, and transcriptomics—we elucidated a highly robust molecular fingerprint of TDF exposure. Crucially, we identified that the active metabolite inhibits complex V (ATP synthase), and that TDF treatment causes rapid, dose-dependent loss of complex V activity and expression. Moreover, we found evidence of complex V suppression in kidney biopsies from humans with TDF toxicity. Thus, we demonstrate an effective and convenient experimental approach to screen for disease relevant functional defects in kidney cells in vitro, and reveal a new paradigm for understanding the pathogenesis of a substantial cause of nephrotoxicity. Graphical Abstract: